Validation of Pro-WEFI conducted in Bangladesh - Adam, Rahma; Rajaratnam, Surendran (2024)
This folder contains outputs from a validation study of Pro-WEFI tool conducted in Bangladesh in 2022. It includes the study tools, dataset and Stata do files.